KUALITAS MUFFIN DENGAN KOMBINASI TEPUNG SORGUM (Sorghum bicolor) DAN TEPUNG KACANG MERAH (Phaseolus vulgaris) - Gunawan, Anita; Pranata, Franciscus Sinung; Swasti, Yuliana Reni (Universitas Sebelas Maret (UNS), 2021)
Muffin is a cake whose manufacturing process is very easy, practical and fast. In this study, muffin with a combination sorghum flour and red bean flour are expected to be preferred because have a good nutritional content, especially fiber content. The purpose of this study was to determine the effect of adding sorghum and red bean flour to the chemical, physical, and microbiological qualities of the muffins and to determine the best concentration of adding sorghum flour and red bean flour. The experimental design in this study was a completely randomized design with variations of wheat flour, sorghum flour and red bean flour as much as 100: 0: 0 (K), 65: 30: 5 (A), 70:20:10 (B) and 75. : 10:15 (C). The parameters tested in this study included chemical, physical, and microbiological qualities. The results showed that the muffins with the best treatment were the combination of wheat flour, sorghum flour and red bean flour 75: 15: 10%. Muffins with the best treatment containing 25.99% water content, 1.46% ash content, 20.15% fat content, 9.02% protein content, 39.62% carbohydrate content, 12.11% insoluble fiber content, soluble fiber content of 3.92%, texture 133.5 g and microbiological tests which include total plate and yeast mold numbers that meet the SNI standards for sweet bread (SNI 01-2840-1995).